Nurse-led web-based self-management program to improve patient activation and health outcomes in patients with chronic low back pain: an acceptability and feasibility pilot study - Richard L. Skolasky; Sarah Nolan; Raven Pierre; Paige Vinch; Janiece L. Taylor (BMC, 2024)
Abstract Background Patients with chronic low back (cLBP) pain report reduced physical function and ability to participate in social roles and are more likely to use opioid pain medications. While self-management interventions have been shown to support these patients, their effectiveness has been limited due to poor patient engagement. "Patient activation" encompasses the skills, knowledge, and motivation that a person has to manage their health. Supporting patient activation may improve the effectiveness of self-management for cLBP. Methods In this single-masked pilot study of adults with cLBP, patients were randomized to receive either no intervention (control) or 6 weekly sessions of an evidence-based web-based self-management program (SMP) with or without health behavior change counseling (HBCC) using motivational interviewing. Participants were assessed at baseline and at 12 and 26 weeks using the Patient Activation Measure, Oswestry Disability Index and PROMIS physical function, social role participation, and pain interference. We assessed acceptability and feasibility based on recruitment, session attendance, and follow-up. Results Of 187 individuals screened, 105 were eligible and 34 were randomized to control (n = 12), SMP (n = 4), or SMP + HBCC (n = 18). The population had 19 women, 22 patients married or living with significant other, 13 Black or African American patients, and 4 Hispanic or Latino patients. Participants had a mean (SD) Oswestry Disability Index score of 42 (12), moderate impairments in physical function (40 (6.6)) and social roles (45 (10)), and moderately severe pain interference (61 (6.7)). Of 22 participants receiving SMP sessions, 20 participated in at least 1, 15 participated in at least 3, and 7 participated in all 6 sessions. Loss to follow-up was 6 over the 26-week study. Participants in the SMP and SMP + HBCC groups had at least medium effect size improvements in Patient Activation Measures and small-to-medium effect size improvements in Oswestry Disability Index scores and physical function and large effect size improvement in social roles at 12 weeks. Improvements persisted in the SMP + HBCC group at 26 weeks. Conclusions A web-based SMP is acceptable and feasible in this population. Participants who received augmentation with HBCC had persistent improvements in health outcomes at 26 weeks. Trial Registration ClinicalTrials.gov Identifier NCT06236529 (2/1/2024 - retrospectively registered). Level of Evidence 3.